Alternatives for vascular reconstruction in pediatric living donor liver transplantation. (13th May 2016) - Neto, Joao Seda; Fonseca, Eduardo A.; Cândido, Helry L.; Pugliese, Renata; Feier, Flavia H.; Kondo, Mario; Azambuja, Rodrigo L.; Chapchap, Paulo
Abstract: Many publications discuss the various strategies for vascular reconstruction (VR) in pediatric LDLT. Having knowledge of alternative techniques is helpful in planning transplants. This article presents three case reports that illustrate some of the alternative techniques for HV, PV, and HA reconstruction in pediatric LDLT. It also reviews the available alternative strategies reported for VR in pediatric LDLT. In the first case, a 13‐month‐old girl presented a PRETEXT III HB with invasion of the retrohepatic vena cava. An LLS graft HV was anastomosed to a DD iliac vein graft and subsequently implanted in a "standard" fashion in the recipient. In the second case, a 44‐month‐old boy presented with multifocal HB and portomesenteric thrombosis and the portal inflow was done through a renoportal anastomosis. In the third case, a 22‐month‐old child with a failed Kasai procedure had extensive HA thrombosis. The HA reconstruction was performed with an interposition of the recipient's IMV graft. The use of alternative techniques for VR in pediatric LDLT is paramount to the success of such a complex procedure. Imaging studies can help transplant surgeons outline surgical strategies and define the best technique to be used in each case.